1976
DOI: 10.1007/bf01145416
|View full text |Cite
|
Sign up to set email alerts
|

Flavonole und Flavone der Gem�searten

Abstract: Green leaves of leek and chive mainly contain kaempferol glycosides, with mono- and di-glycosides dominating in leek and di- and tri-glycosides in chive. In leek glucose is dominant as sugar component compared to xylose; in chive we found glucose and galactose. Kaempferol-3-beta-D-glucoside and kaempferol-3-xylosyl-beta-D-glucoside were isolated from leek and the 3-beta-D-glucosides of kaempferol, quercetin and isorhamnetin as by-glycosides from chive. In leek traces of quercetin-3-glucoside were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Price and Rhodes have reported that 80-85% of total flavonoids in onion species belong to quercetin glucosides (quercetin-3,4 -O-diglucoside (QDC) and quercetin-4 -O-monoglucoside (QMG)) [78]. Furthermore, 3-β-D-glucosides of quercetin, kaempferol, and isorhamnetin were found in the green leaves of A. schoenoprasum [79]. On the other hand, by examining the content of flavonoids (by HPLC) in 70% ethanol extracts of A. fistulosum and A. ursinum, the presence of kaempferol in the non-hydrolyzed and hydrolyzed extracts of A. fistulosum and only in hydrolyzed samples of A. ursinum flowers and leaves was determined.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Price and Rhodes have reported that 80-85% of total flavonoids in onion species belong to quercetin glucosides (quercetin-3,4 -O-diglucoside (QDC) and quercetin-4 -O-monoglucoside (QMG)) [78]. Furthermore, 3-β-D-glucosides of quercetin, kaempferol, and isorhamnetin were found in the green leaves of A. schoenoprasum [79]. On the other hand, by examining the content of flavonoids (by HPLC) in 70% ethanol extracts of A. fistulosum and A. ursinum, the presence of kaempferol in the non-hydrolyzed and hydrolyzed extracts of A. fistulosum and only in hydrolyzed samples of A. ursinum flowers and leaves was determined.…”
Section: Phenolic Compoundsmentioning
confidence: 99%